2023
DOI: 10.18697/ajfand.116.22640
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing women’s acceptance of palm weevil larvae for consumption in peri-urban communities in the Ashanti region, Ghana

Abstract: For Ghanaian women of reproductive age (WRA), anemia remains a pressing issue. Currently, at the global level, anemia affects 35% of this population according to the most recent “State of Food Security and Nutrition in the World” report. In Ghana, anemia is mostly associated with iron deficiency and, if left untreated, could result in several adverse outcomes including severe fatigue and exhaustion resulting in decreased work productivity, neurocognitive impairment, and complications with chronic kidney diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…In another study focused on women, Chamoun et al [6] explored the feasibility of addressing maternal anemia through promoting the consumption of edible insects, such as palm weevil larvae. In the Ashanti region of Ghana where this study was conducted, she observed a positive perception of palm weevil larvae.…”
mentioning
confidence: 99%
“…In another study focused on women, Chamoun et al [6] explored the feasibility of addressing maternal anemia through promoting the consumption of edible insects, such as palm weevil larvae. In the Ashanti region of Ghana where this study was conducted, she observed a positive perception of palm weevil larvae.…”
mentioning
confidence: 99%